Bilateral thalamic and mesencephalic infarctions with hypopituitarism as long-term complications postradiotherapy: A case report. Issue 34 (August 2018) - Hui, Liang; Shijun, Hu; Tao, Liu; Guoqiang, Wen; Shixiong, Huang
Abstract: Background: Radiation is widely used as the first-line treatment for nasopharyngeal carcinoma (NPC) and improves survival. Nevertheless, radiation also places the patients at risk of radiation-induced adverse effects, such as transient ischemic attack, ischemic stroke, hypopituitarism, and cranial nerve and temporal lobe dysfunction. Case report: A 54-year-old woman who had undergone radiation treatment for NPC 14 years earlier and had no cerebrovascular risk factors, visited our department 4 days after sudden onset of consciousness disturbance. Brain magnetic resonance imaging (MRI) revealed bilateral thalamic and left mesencephalic infarctions with empty sella. Meanwhile, MR angiography showed narrowing in the bilateral posterior cerebral artery. Furthermore, laboratory tests showed low total triiodothyronine (T3), thyroxine (T4), free T3, free T4, luteinizing hormone, estradiol, follicle-stimulating hormone, and serum natrium and normal thyroid-stimulating hormone, which indicated radiation-related hypopituitarism. Serologically, she had low hemoglobin, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, ferritin, and serum iron levels and elevated transferrin, manifesting microcytic anemia. The treatment, including aspirin, atorvastatin, levothyroxine, prednisone, saline infusion, and chalybeate, promoted the patient's recovery. Conclusion: To our knowledge, this is the first report of bilateral thalamic and mesencephalic infarction together with hypopituitarism following radiotherapy for NPC.